1975
DOI: 10.1210/endo-96-2-508
|View full text |Cite
|
Sign up to set email alerts
|

A Renin-like Activity in Pineal Gland and Hypophysis

Abstract: The presence and distribution of renin-like activity in hypophysis, pineal gland and some neural tissues were studies in both normal and salt-loaded rats. The Boucher micromethod was used to detect enzymatic activity. In normal rats both the pituitary and pineal glands contained significantly higher values of renin-like activity than did the other tissues examined. In salt-loaded animals there was a significant decrease of the renin-like activity of the glandular tissue while in the other brain areas the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
1

Year Published

1981
1981
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…The results are partly in agreement with data reported by Haulica et al (21), who found that an acute intravenous NaCl load reduced renin activity in the pineal gland and in the pituitary. They also reported that this maneuver stimulated renin activity in cortex, hypothalamus, and brain stem, a result inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are partly in agreement with data reported by Haulica et al (21), who found that an acute intravenous NaCl load reduced renin activity in the pineal gland and in the pituitary. They also reported that this maneuver stimulated renin activity in cortex, hypothalamus, and brain stem, a result inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Renin activity was widely present in brain, although 8 (19)(20)(21) and hogs (9). The presence of renin activity in the posterior pituitary has been reported in rats (19,20), but not in hogs.…”
Section: Discussionmentioning
confidence: 95%
“…Renin-like activities have been observed in various endocrine tissues (16,17). However, whether such activities are due to specific renin or to nonspecific proteolytic activity has been the subject ofmuch discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Slater et aL (4) reported immunoreactive renin in both anterior and posterior lobes of human pituitary by an immunohistochemical technique. Haulica et aL (1) reported that the renin-like activity in the posterior lobe of rat pituitary is three times higher than that in the anterior lobe. Day and Reid (2), and Hackenthal et al (6), however, suggested that the renin-like activity in pituitary may be cathepsin D.…”
mentioning
confidence: 97%
See 1 more Smart Citation